Improving Character Education Strengthening Through Edmodo-Based E-Learning - Makhroji, Makhroji; Imran, Imran (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The application of technology in the educational process is a challenge for the next generation to face the revolution in the development of learning and technology. One of the applications is based on e-Learning through edmodo. The application of technology is also expected to be in harmony with the growth of the character of the nation, especially the character of students. The research objective is to find out the improvement of character education strengthening through edmodo-based e-learning learning. The research method is action research. The results of this study have increased the value of honest character, discipline character and responsibility character from cycle I and cycle II. It can be concluded that the Edmodo application can be used as a learning medium for e-learning.